A Linguistic Approach To Teaching English For Specific Purposes For Food And Beverage Service Students - Anggayana, I Wayan Agus; Asriyani, Retny; Lindawati, Ni Putu (International Journal of Linguistics and Discourse Analytics, 2024)
This study explores a linguistic approach to teaching English for Specific Purposes (ESP) tailored for food service students in hospitality programs. The hospitality industry requires a specific set of English communication skills, especially in food service, where language proficiency directly impacts customer satisfaction. This research examines how a linguistic framework enhances learning and helps students develop specialized vocabulary, listening, and speaking skills critical to their future careers. The findings demonstrate that a linguistic approach to ESP significantly improves students' communication ability in food service environments. The study concludes by emphasizing the importance of ESP in preparing students for professional competence in the hospitality industry. Mastery of vocabulary and communication skills is essential for students pursuing careers in the hospitality industry, where clear and effective interaction with clients and colleagues is crucial. A Linguistic Approach to Teaching English for Specific Purposes (ESP) offers a comprehensive solution to these needs, focusing on the practical application of language in real-world situations. The findings emphasize the importance of tailored ESP education in preparing hospitality students for professional competence, with a focus on practical language application that directly impacts customer satisfaction. This linguistic approach offers a well-rounded solution for developing essential communication skills, positioning students to succeed in the dynamic hospitality industry